2016
DOI: 10.1176/appi.ps.201600340
|View full text |Cite
|
Sign up to set email alerts
|

Finland in Boston? Applying Open Dialogue Ideals on a Psychotic Disorders Inpatient Teaching Unit

Abstract: This column argues for the importance of patient-centered approaches in psychiatry and describes the development and pilot implementation, inspired by the Finnish Open Dialogue model, of a program designed to increase the "patient-centeredness" of an inpatient psychotic disorders unit at McLean Hospital. Preliminary evidence shows that an inpatient psychiatry unit can implement patient-centered changes that are acceptable to staff and patients without additional cost or time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…Open dialogue has been fostered as a means of treating hospitalised patients as equals (Seikkula, 2011), focussing on strengthening personal resources and normalising individual situations rather than focussing on regressive behaviour. Rosen and Stoklosa (2016) found that open dialogue can be used as an effective form of inpatient treatment in patient-centred care.…”
Section: Discussionmentioning
confidence: 99%
“…Open dialogue has been fostered as a means of treating hospitalised patients as equals (Seikkula, 2011), focussing on strengthening personal resources and normalising individual situations rather than focussing on regressive behaviour. Rosen and Stoklosa (2016) found that open dialogue can be used as an effective form of inpatient treatment in patient-centred care.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its potential as an alternative approach to mental health care, there has been increasing interest in Open Dialogue outside Finland. Over the last two decades, Open Dialogue has been introduced in health care services across Scandinavia, the United Kingdom, Italy, Germany, and the United States (for examples see Brottveit, ; Buus et al, ; Gordon et al, ; Holmesland, ; Razzaque & Wood, ; Rosen & Stoklosa, ). As Open Dialogue expands to settings outside of Finland, there is a need for contextually specific local adaptions of the approach and a need to understand successful implementation strategies, including Australian applications.…”
Section: Faq 1 Don't We Do This Already?mentioning
confidence: 99%
“…While in conventional psychiatric practice, young people are usually seen by different professionals in separate sessions, Open Dialogue is a resource-oriented model of therapeutic intervention that promotes collaborative integrated care by means of network meetings between patient, family and social network members, and therapists, and a non-directive psychotherapeutic stance (Anderson andGehart, 2006, Gordon et al, 2016, Priebe et Rosen and Stoklosa, 2016). It was gradually developed in Finland during the 1980s to facilitate shared care service delivery in Western Lapland (Buus et al, 2017).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%